Early‐TIPSS placement prevents rebleeding in high‐risk patients with variceal bleeding, without improving survival. Issue 9 (17th September 2014) - Rudler, M.; Cluzel, P.; Corvec, T. L.; Benosman, H.; Rousseau, G.; Poynard, T.; Thabut, D.
Summary Background Early‐TIPSS (transjugular intrahepatic portosystemic shunt) placement may improve rebleeding and reduce 1‐year mortality, compared to standard management in high‐risk patients with cirrhosis and variceal bleeding. Aim To obtain external validation of this therapeutic approach. Methods We performed a prospective study including all consecutive patients with Child–Pugh C 10–13 cirrhosis or Child–Pugh B with active bleeding at endoscopy admitted to our ICU between March 2011 and February 2013 for variceal bleeding. TIPSS were placed within 72 h after stabilisation. Patients were matched for gender, age, Child–Pugh score, MELD score and to patients from a historical cohort hospitalised before March 2011. Results 31/128 patients with cirrhosis (77.4% men, mean age 53.2 ± 9.0 years old, MELD score 20.9 ± 6.9, Child–Pugh C: 77.4%) admitted for acute variceal bleeding between March 2011 and February 2013 (TIPSS+ group) were matched to 31 historical patients (TIPSS− group). Uncontrolled bleeding occurred in 1/31 patients in the TIPSS+ group vs. 2/31 patients in TIPSS− group (P = 0.55). The 1‐year probability of being free of rebleeding was higher in the TIPSS+ group (97% vs. 51%, P < 0.001). Actuarial 1‐year survival was not different between the two groups (66.8 ± 9.4% vs. 74.2 ± 7.8%, P = 0.78). Acute cardiac failure occurred more frequently in the TIPSS+ group (25.8% vs. 6.4%, P = 0.03). Conclusions Early‐TIPSS placement effectively prevents rebleeding in high‐risk patients with variceal bleeding but does not significantly improve survival. This might be due to the high proportion of patients with Child–Pugh C cirrhosis in our series. Cardiac failure may play a role and must be investigated before the procedure, when possible.